THE RELEVANCE OF PANCASILA JUSTICE IN IMPLEMENTING STATE ADMINISTRATIVE COURT DECISIONS - Dani Sintara; Marzuki Marzuki (UNISSULA, 2021)
Administrative law in its development has two dimensions, on the one hand guarantee the realization of state power balance and includes the relationship between the relevant state institutions and on the other hand guarantee the harmonization between the function and duties of the state with the ideals of the nation, it is also clear that the administrative law is a realized media From the concept of limitation of power as it becomes the core of a constitutional democracy, the method of approaching normative juridical, the results of the study stated that the issue of the implementation of the State Administrative Court's court ruling depend on the moral ethics of public officials, has made a state administrative court ruling difficult to exceed in reality in society. Such conditions have contrary to the principle of the Litit of the Oportet which requires every case there must be finally because the purpose of the case of the court to the court is certainly to get a solution. Pancasila justice is a basic principle must be implemented in the decision of the State Administrative Court to realize the certainty of law and justice needed by the community.